Clinicopathological profile of ovarian tumors in the age group 10-20 years - V., Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adolescence is the period of transition from childhood to adulthood. 1% neoplasm occurs in this age group below 17 years, of this, 3% are ovarian neoplasms. Aim was to study retrospectively the clinicopathological profile and outcome of ovarian tumors in the age group 10-20 years in Government Medical College, Kottayam, Kerala, India from January 2008 for six years. Methods: Fifty Patients who have undergone laparotomy in this institution during the period were taken for study. Data regarding age, mode of presentation, diagnostic methods, treatment and histopathology were recorded. Follow-up was also taken into consideration. Patients with polycystic ovary, corpus luteal cyst, follicular cyst and endometriotic cyst are excluded. Results: Majority of the patients fall between the age group 15-20 years. Major clinical presentation was pain (40%), followed by abdominal mass. Laparotomy was done for all cases except three where laparoscopy was done. Imprint cytology taken for 3 cases. Histopathology showed malignant tumors in 6 cases and benign tumors in 44 cases. Epithelial tumors outnumbered germ cell tumors. Conclusions: This study shows the predominance of epithelial neoplasms in the age group 10-20 years. Proportion of malignancy is 12%.